Single-atom Pt-doped ceria nanozymes mitigate myocardial ischemia reperfusion injury via cardiomyocyte-targeted uptake and suppression of reactive oxygen species - Aoyang Pu; Woo-Sup Sim; Yunseong Ji; Amal George Kurian; Jung-Hwan Lee; Thi Van Anh Bui; Yimin Lai; Hyesoo Hwangbo; Huanhuan Sun; Hae-Won Kim; Hun-Jun Park; Kiwon Ban (Bioactive Materials, 2025)
The primary treatment for myocardial infarction (MI) is restoring blood flow to the obstructed coronary artery. However, this approach can paradoxically generate reactive oxygen species (ROS), leading to secondary ischemia-reperfusion (IR) injury. Multifunctional nanomaterials present a promising alternative for managing IR injury, offering benefits including cost-effectiveness, robust catalytic stability, and customizable properties that surpass traditional antioxidants. This study explores single-atom Pt-doped ceria nanozymes (Pt@CeNZ) with multi-enzyme mimetic functions facilitated by atomically dispersed Pt. The nanozymes effectively eliminate excess ROS in cardiomyocytes, thereby enhancing cell viability. Notably, Pt@CeNZ demonstrates significantly higher uptake in cardiomyocytes, underscoring its potential as a targeted nanotherapeutic for cardiac tissues. In vivo studies further confirm that Pt@CeNZ treatment substantially reduces infarct size and improves cardiac function following IR injury, without inducing long-term toxicity or inflammation. These findings position Pt@CeNZ as a highly promising heart-targeting nanotherapeutic with potential applications in the acute and long-term treatment of cardiac injuries.